Aryl or heteroaryl substituted aminal derivatives of HCV NS5A inhibitor MK-8742. Issue 15 (1st August 2016) - Yu, Wensheng; Coburn, Craig A.; Nair, Anilkumar G.; Wong, Michael; Rosenblum, Stuart B.; Zhou, Guowei; Dwyer, Michael P.; Tong, Ling; Hu, Bin; Zhong, Bin; Hao, Jinglai; Ji, Tao; et al.
Graphical abstract: Abstract: Herein we describe our research efforts around the aryl and heteroaryl substitutions at the aminal carbon of the tetracyclic indole-based HCV NS5A inhibitor MK-8742. A series of potent NS5A inhibitors are described, such as compounds45 –47, 54, 56, and65, which showed improved potency against clinically relevant and resistance associated HCV variants. The improved potency profiles of these compounds demonstrated an SAR that can improve the potency against GT2b, GT1a Y93H, and GT1a L31V altogether, which was unprecedented in our previous efforts in NS5A inhibition.